The German Labor Market Reforms and Post-Unemployment Earnings - Engbom, Niklas (IMF Working Papers; Working Paper ;, 2015)
In 2003-05, Germany undertook extensive labor market reforms which were followed by a large and persistent decline in unemployment. Key elements of the reforms were a drastic cut in benefits for the long-term unemployed and tighter job search and acceptance obligations. Using a large confidential data set from the German social security administration, we find that the reforms were associated with a fall in the earnings of workers returning to work from short-term unemployment relative to workers in long-term employment of about 10 percent. We interpret this as evidence that the reforms strengthened incentives to return to work but, in doing so, they adversely affected post re-entry earnings.